1998
DOI: 10.2170/jjphysiol.48.33
|View full text |Cite
|
Sign up to set email alerts
|

Does Electrical Stimulation of the Sciatic Nerve Prevent Suspension-lnduced Changes in Rat Hindlimb Bones?

Abstract: Osteoporosis due to mineral loss is a major health problem resulting from long-term spaceflight. The development of a suitable countermeasure is essential because an advanced decrease in bone density could be irreversible. Therefore the current study was performed to test our hypothesis that the loading of bones by electrical stimulation-induced muscle contraction may prevent the mineral loss caused by gravitational unloading and bone growth will be maintained. During 10 d of hindlimb suspension, electrical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…The unloading-related bone loss was not prevented by low-frequency stimulation using a 10-Hz bipole rectangular current with intensity of 0.2-8 mA (Zerath et al, 1995). However, Wei et al (1998) reported that suspension-related decrease in bone mineral content was prevented by high-frequency train stimulation (at 50 and/or 100 Hz, 8 h/day) through sciatic nerve. Although the importance of mechanical loading on bone growth is generally accepted, the results obtained in the present study suggest that well-balanced mechanical stress, induced by ankle flexors and extensors, is essential for normal growth of leg bones.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The unloading-related bone loss was not prevented by low-frequency stimulation using a 10-Hz bipole rectangular current with intensity of 0.2-8 mA (Zerath et al, 1995). However, Wei et al (1998) reported that suspension-related decrease in bone mineral content was prevented by high-frequency train stimulation (at 50 and/or 100 Hz, 8 h/day) through sciatic nerve. Although the importance of mechanical loading on bone growth is generally accepted, the results obtained in the present study suggest that well-balanced mechanical stress, induced by ankle flexors and extensors, is essential for normal growth of leg bones.…”
Section: Discussionmentioning
confidence: 98%
“…Electrical stimulation of leg muscles of unloaded rats is utilized to prevent bone loss (Wei et al, 1998;Zerath et al, 1995). The unloading-related bone loss was not prevented by low-frequency stimulation using a 10-Hz bipole rectangular current with intensity of 0.2-8 mA (Zerath et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In rat models of tibial fractures, severing of the sciatic nerve to the fractured leg may have positive systemic effects on other parts of the skeleton suggesting that the nervous system may be involved in bone formation other than locally through the effect on the muscles (10). Furthermore, electrical stimulation of a severed sciatic nerve may preserve bone mineral in an otherwise immobilized rat leg suggesting that the mechanical load of the muscles may compensate for the immobilization (11). In spinal cord injury, patients with cervical lesions and paralysis have a lower bone mineral in the femoral neck than patients with lumbar lesions and spastic paresis (2).…”
Section: Introductionmentioning
confidence: 99%
“…EMS is a non-drug therapy. Wei et al (10) reported that loading by stimulation-induced muscle contraction at high frequencies was beneficial for the maintenance of bone growth or the prevention of mineral loss, or both, during hindlimb suspension in rats. In the present study, TC was used for dual-label mineralizing bone formation and bone growth.…”
Section: Discussionmentioning
confidence: 99%